University proceedings. Volga region. Natural sciences - P.O. Pavlov (Известия высших учебных заведений. Поволжский регион: Естественные науки)
Background. Monitoring of key species in the national park is an integral part of its functioning. One of these species for the “Sengileevskie Gory” is the steppe marmot. The purpose of this study is to identify the current state of steppe marmot settlements in terms of the environmental status of the territories. Materials and methods. The material was collected for the period from 2023–2024, groundhog accounting was carried out in the spring and summer, in the morning hours, when the animal is most active, the collection of material was carried out during a walking route. The estimation of the number of marmots in settlements was not carried out using the direct accounting method of numbers at trial sites with subsequent extrapolation, but was calculated using the following indicators: the number of family plots with full accounting in the settlement and the average number of animals in the family grouping. The average number of animals in the family was calculated based on the data of groundhog accounting in Ulyanovsk region. For 16 275 family groups, this figure was 3.79 os/per 1 family. Results. Based on the results of the work done, we can observe an increase in the number of animals in all the surveyed settlements. Conclusions. The conservation status of the National Park “Sengileevskie Gory” undoubtedly has a beneficial effect on the number of steppe marmots and the state of their populations as a whole.